COMPILATION OF QURANIC VERSES ON HEARING SCIENCES AND HEARING IMPAIRMENT - Thani, Akmal Abdul Wafiy Mohd; Rahmat, Sarah; Hashi, Abdurezak Abdulahi (International Journal of Allied Health Sciences, 2019)
Introduction: The Qur’an, which is the founding scripture of the Islamic teaching, together with the tradition of Prophet Muhamad (s. a. w.), functions as the ultimate guide for Muslim life, both in spiritual life and social order. Its teachings cover guidelines on religious practices, descriptive indications on given natural phenomena, as well as principles of managing conditions of life. Though the Qur’an is not a book of biology neither it is a book of human anatomy, yet its teachings incorporate meaningful indications and illustrations on the functions and the roles of human organs in terms of knowledge acquisition and understanding the meaning of life. This study aims to compile the Qur’anic verses related to hearing sciences and analyse its meaning in line with the theme of scientific knowledge of audiology. Methods: This study employs scoping review methods. Systematic search was performed using 34 keywords of ‘ear’, ‘ears’, ‘deaf’, ‘deafness’, ‘deafen’, ‘deafening’, ‘deafer’, ‘deafest’, ‘deafly’, ‘hear’, ‘hears’, ‘hearing’, ‘heard’, ‘unheard’, ‘hearer’, ‘heareth’, ‘aural’, ‘auditory’, ‘listen’, ‘listens’, ‘listening’, ‘listened’, ‘listener’, ‘heed’, ‘heeds’, ‘heeding’, ‘heeded’, ‘heeder’, ‘heedless’, ‘unheedful’, ‘hearken’, ‘hearkens’, ‘hearkening’ and ‘hearkened’, via two Qur’anic search engine which is Search Truth and Search the Quran (https://www.searchtruth.com/ and http://search-the-quran.com/). The Qur’anic verses that met the inclusion criteria were analysed using thematic analysis to determine the themes. The thematic analysis was conducted in reference to Tafseer Ibn Kathir and Tafseer ar Rahman, along with expert committee discussion. Results: Out of 250 identified verses containing relevant keywords, only 195 verses met the inclusion criteria and were further analysed. Thematic analysis on these final verses yields 4 themes which are ‘the obstacle of hearing’, ‘manners of hearing’, ‘the development of hearing system’ and ‘the hearing attributes of God (Allah)’. Conclusions: The findings of this study showed that hearing sciences has been addressed in great details in the Qur’an. This study may serve as future reference in Audiology/ hearing related field for both Muslim and non-Muslim scientist specifically, and for all Muslims in general.